The role of society and family in adolescents’ disaster resilience: A qualitative study - Mohammad Ali Rezaei; Neda Mohammadinia (BMC Public Health)
Abstract Background Resilience is a person’s ability to adapt to life problems and crises and is influenced by many factors. Due to the increase in the number and severity of disasters, disaster preparedness policies should be developed at different levels and among multiple groups. More attention should be given to vulnerable groups. The aim of the present study is exploring the role of society and family in adolescents’ disaster resilience. Methods The present study was conducted using a qualitative method with content analysis approach. The participants were 28 high school teachers in Bam city, who were selected based on the purpose, to be the least 10 years of age at the time of the Bam earthquake, willingness and ability to provide experiences, active participation in this study and filling the written consent form. Sampling was continued until data saturation. The data were collected via in-depth and semi-structured interviews and analyzed with the steps suggested by Granheim and lundman method. Results The data analysis revealed 452 open codes, 192 conceptual codes after integration, 14 subcategories, and 4 categories of factors affecting resilience against disasters. The categories included resilience strengthening and restraining factors in the family and society. Conclusion The results of the present study revealed the importance of family and society function in adolescent resilience, which can be used to help crisis management practitioners and decision makers plan community preparedness and improving Support Systems especially in schools, before disasters or Situational and predictable crisis.